Two Asian dreamers, doers - Quayum, Mohammad Abdul (International Islamic University Malaysia, 2013)
Examines the contributions and significance of two of the best Asian writers of the modern era, South Asia's Rokeya Sakhawat Hossain (1880-1932) and Southeast Asia's Edwin Thumboo (1933-). It looks at their similarities and differences in outlook and scope of writing.